Classification and analysis of the structures of tillage working bordies - Bereza, Olena; Береза, Олена Юріївна; Chernii, Yevhen; Черній, Євген; Maliehina, Anastasiya; Малєгіна, Анастасія (Scientific Publishing Center “Sci-conf.com.ua”, 2024)
During the restoration of forest plantations, in places of previous fellings, as well as when clearing areas for forestry lands and infrastructure facilities, stump removal works play an important role. 2. The most acceptable of the existing methods of stump removal is mechanical uprooting of individual stumps, since this preserves the fertile soil layer and causes the least damage to the ecosystem. 3. When uprooting individual stumps, the most acceptable is the use of a stump remover with digging jaws of the grab type mechanism, which allows creating significant efforts for digging the stump and allows the stump to be loaded into the vehicle using the same working body. В роботі розглянуто питання значення, класифікації та особливостей ґрунтообробних робочих органів для роботи в умовах очищення лісових ділянок від пнів при освоєнні ділянок під сільськогосподарські угіддя.
Класифікація та аналіз структур грунтообробних робочих органів
Keywords: Uprooting machines; корчувальні машини; working body; робочий орган; translational movement; поступальний рух; combined movement; комбінований рух